2000
DOI: 10.1074/jbc.275.14.10182
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate and Intracellular pH Regulate the ROMK1 Potassium Channel via Separate but Interrelated Mechanisms

Abstract: ROMK channels are responsible for K؉ secretion in kidney. The activity of ROMK is regulated by intracellular pH (pH i ) with acidification causing channel closure (effective pK a ϳ6.9). Recently, we and others reported that a direct interaction of the channels with phosphatidyl-4,5-bisphosphate (PIP 2 ) is critical for opening of the inwardly rectifying K ؉ channels. Here, we investigate the relationship between the mechanisms for regulation of ROMK by PIP 2 and by pH i . We find that disruption of PIP 2 -ROMK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 32 publications
4
84
1
Order By: Relevance
“…It has been shown that reduction in PIP 2 binding can shift the effective pK a for pH gating in Kir1.1 channels to more alkaline values. This was based on the finding that low PIP 2 concentrations in the membrane or reduction in PIP 2 binding, as seen with a mutant channel (R188Q), increased the pH sensitivity (15). We found that PIP 2 binding is already saturated for WT Kir1.1 channels since addition of exogenous PIP 2 caused no additional shift in the pK a .…”
Section: Arg-54 In the N Terminus Of Kir62 Is A Major Determinant Fomentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that reduction in PIP 2 binding can shift the effective pK a for pH gating in Kir1.1 channels to more alkaline values. This was based on the finding that low PIP 2 concentrations in the membrane or reduction in PIP 2 binding, as seen with a mutant channel (R188Q), increased the pH sensitivity (15). We found that PIP 2 binding is already saturated for WT Kir1.1 channels since addition of exogenous PIP 2 caused no additional shift in the pK a .…”
Section: Arg-54 In the N Terminus Of Kir62 Is A Major Determinant Fomentioning
confidence: 99%
“…It has been proposed that PIP 2 binding to Kir1.1 alters the pK a for pH gating (15). Thus, we tested whether the absence of the N-terminal PIP 2 site might be a prerequisite for Kir1.1 channels to operate in the physiological pH range (6.8 -7.5).…”
Section: Arg-54 In the N Terminus Of Kir62 Is A Major Determinant Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Activity of the Kir1.1 channel is directly regulated by intracellular pH, protein kinase A, protein kinase C, phosphatidylinositol-4,5-biphosphate, and WNK4 (serine-threonine kinase 4 with no lysine) (8 -11). Inhibition of protein kinase A activity or phosphatidylinositol-4,5-biphosphate production shifts the channel sensitivity toward more alkaline pH levels (12,13).…”
Section: Kir11 (Romk1) Is a Member Of The Inward Rectifier Kmentioning
confidence: 99%
“…For the TRPM7 channel, cation screening of membrane phosphatidylinositol(4,5)bisphosphate (PIP 2 ) charges appears to be important for polyvalent cation-mediated regulation of channel activity. Similarly, PIP 2 greatly influences the open state of ROMK, and this effect can be modulated by internal pH (6). Thus, multiple types of salt bridge interactions may be contributing to the very complex behavior of channels to changes in cytosolic pH.…”
Section: The C-terminal Arginine In the Rxr Forms An R-e Ion Pair Betmentioning
confidence: 99%